Antara Kepastian dan Keadilan: Kritik Sosio-Legal terhadap Orientasi Penegakan Hukum di Indonesia - Virginia Usfunan; Yudith Bana; Efatha F.B. Duarte (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Law in a modern rule-of-law state is normatively intended to ensure legal certainty, justice, and social utility. However, in the context of law enforcement practices in Indonesia, these objectives are rarely realized in a balanced manner. This article aims to critically examine the tendency of law enforcement to position law primarily as an instrument of procedural order rather than as a means of achieving substantive justice. Employing a qualitative socio-legal approach combined with legal-philosophical analysis, this study is based on a critical review of legal literature and conceptual examination of law enforcement practices. The findings indicate that the dominance of legal formalism and proceduralism has oriented law enforcement toward rigid administrative certainty, while considerations of substantive justice remain marginal. Legal processes function not only as mechanisms for enforcing norms but also, in certain contexts, as forms of implicit punishment that disproportionately affect socially and economically vulnerable groups. This article argues that without a paradigmatic reorientation that places substantive justice and Pancasila-based legal values as operational ethical foundations, law will continue to function predominantly as an instrument of order rather than as a corrective mechanism for structural injustice. Keywords: law enforcement; substantive justice; legal order; socio-legal studies Abstrak Hukum dalam negara hukum modern secara normatif diarahkan untuk menjamin kepastian, keadilan, dan kemanfaatan. Namun, dalam praktik penegakan hukum di Indonesia, orientasi tersebut kerap tidak terwujud secara seimbang. Artikel ini bertujuan menganalisis secara kritis kecenderungan penegakan hukum yang lebih menempatkan hukum sebagai instrumen ketertiban prosedural dibandingkan sebagai sarana pencapaian keadilan substantif. Penelitian ini menggunakan pendekatan kualitatif dengan desain sosio-legal dan analisis filosofis hukum, melalui telaah literatur hukum dan kajian konseptual terhadap praktik penegakan hukum. Hasil penelitian menunjukkan bahwa dominasi legal-formalisme dan proseduralisme telah mendorong penegakan hukum beroperasi dalam kerangka kepastian administratif yang kaku, sementara pertimbangan keadilan substantif cenderung terpinggirkan. Proses hukum tidak hanya berfungsi sebagai mekanisme penegakan norma, tetapi juga berpotensi menjadi bentuk penghukuman terselubung yang berdampak tidak proporsional, khususnya bagi kelompok masyarakat dengan posisi sosial dan ekonomi lemah. Artikel ini menegaskan bahwa tanpa reorientasi paradigma penegakan hukum yang menempatkan keadilan substantif dan nilai-nilai Pancasila sebagai dasar etik operasional, hukum akan terus berfungsi terutama sebagai alat ketertiban, bukan sebagai instrumen korektif terhadap ketimpangan sosial. Kata kunci: penegakan hukum; keadilan substantif; ketertiban hukum; sosio-legal